(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Images are an indispensable part of oneâ€™s life .Sharing images of various types on the internet has become a trend as well as mandatory requirement for almost all of us. The digital media provides a worldwide platform for the same. There is always a threat of our private images being illegally reproduced or distributed elsewhere. Colour image watermarking is of utmost importance as colourful figures carry a lot more information than their gray counterparts. To prevent the misuse and protect the copyrights, an efficient solution has been given that can withstand many attacks. This paper aims at encoding of the host image prior to watermark embedding for enhancing the security. The fast and effective full counter propagation neural network helps in the successful watermark embedding without deteriorating the image perception. Earlier techniques embedded the watermark in the image itself but is has been observed that synapses of neural network provide a better platform for reducing the distortion and increasing the message capacity. Â Keywordsâ€” Watermarking , Full Counter Propagation Network, Transform Domain, Discrete Cosine Transform, Encoding